2016
DOI: 10.1177/0883073816658659
|View full text |Cite|
|
Sign up to set email alerts
|

Unique Characteristics of the Photoparoxysmal Response in Patients With Neuronal Ceroid Lipofuscinosis Type 2

Abstract: Photoparoxysmal responses in patients with neuronal ceroid lipofuscinosis type 2 have features which are distinguishing from photoparoxysmal responses seen in other epilepsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…17,18 In the large series of 34 patients with CLN2 disease studied by Jadav et al, 17 for example, only two patients were reported to have PPR at 9 and 15 Hz, but it is unclear how IPS was performed and whether this was carried out in all patients. 13,15 A reduction in the size of evoked discharges is reported to occur at frequencies of 4 Hz or higher, and PPR is sometimes accompanied by muscle twitches in the limbs and/or face. 4 Another study conducted in 18 patients with CLN2 disease using standardized EEG reported a large polyspike response to a single flash of light (evoked by IPS) in all patients in whom this test was performed, 13 but again it is unclear how many patients underwent IPS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…17,18 In the large series of 34 patients with CLN2 disease studied by Jadav et al, 17 for example, only two patients were reported to have PPR at 9 and 15 Hz, but it is unclear how IPS was performed and whether this was carried out in all patients. 13,15 A reduction in the size of evoked discharges is reported to occur at frequencies of 4 Hz or higher, and PPR is sometimes accompanied by muscle twitches in the limbs and/or face. 4 Another study conducted in 18 patients with CLN2 disease using standardized EEG reported a large polyspike response to a single flash of light (evoked by IPS) in all patients in whom this test was performed, 13 but again it is unclear how many patients underwent IPS.…”
Section: Discussionmentioning
confidence: 99%
“…Ambient lighting was minimized (to approximately 50 lux), but was sufficient to facilitate observation of the patient while controlling ocular fixation on the center of the lamp and to note any subtle clinical ictal phenomena. Separate trains of flashes of 5-s duration were used at the following frequencies: 1,2,6,8,10,12,13,14,15,16,17,18,19,20,25,30,40,50, and 60 Hz. Flash trains were separated by a pause of at least 7 s. IPS was used to assess the lowest (starting at, and increasing from 1 Hz) and highest (starting at, and decreasing from 60 Hz) frequencies evoking a generalized PPR.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations